Implementation if PID controller for controlling the liquid level of the coupled tank system - Mohd Izzat, Dzolkafle (2009)
The PID controllers have found wide acceptance and applications in the industries for the past few decades. In spite of their simple structures, PID controllers are proven to be sufficient for many practical control problems. This project presents the PID controller design for controlling liquid level of coupled tank system. These coupled tank liquid level systems are in second order system. The PID Controller will be designed to control the liquid level at tank 1 and design techniques of the PID Controller are then conducted based on developed model. MATLAB has been used to simulate and verified the mathematical model of the controller. Visual Basic 6 has been used to implement the graphical user interface (GUI) and implementation issues for the controller's algorithms will also be discussed. The DAQ card is used for interfacing between hardware and software. The simulated result will be compared with the implemented result.